Ca2+ cycling properties are conserved despite bradycardic effects of heart failure in sinoatrial node cells - Verkerk, Arie O.; van Borren, Marcel M. G. J.; van Ginneken, Antoni C. G.; Wilders, Ronald (Frontiers in Physiology, 2015)
Background: In animal models of heart failure (HF), heart rate decreases due to an increase in intrinsic cycle length (CL) of the sinoatrial node (SAN). Pacemaker activity of SAN cells is complex and modulated by the membrane clock, i.e., the ensemble of voltage gated ion channels and electrogenic pumps and exchangers, and the Ca2+ clock, i.e., the ensemble of intracellular Ca2+ ([Ca2+]i) dependent processes. HF in SAN cells results in remodeling of the membrane clock, but few studies have examined its effects on [Ca2+]i homeostasis. Methods: SAN cells were isolated from control rabbits and rabbits with volume and pressure overload-induced HF. [Ca2+]i concentrations, and action potentials (APs) and Na+–Ca2+ exchange current (INCX) were measured using indo-1 and patch-clamp methodology, respectively. Results: The frequency of spontaneous [Ca2+]i transients was significantly lower in HF SAN cells (3.0 ± 0.1 (n = 40) vs. 3.4 ± 0.1 Hz (n = 45); mean ± SEM), indicating that intrinsic CL was prolonged. HF slowed the [Ca2+]i transient decay, which could be explained by the slower frequency and reduced sarcoplasmic reticulum (SR) dependent rate of Ca2+ uptake. Other [Ca2+]i transient parameters, SR Ca2+ content, INCX density, and INCX-[Ca2+]i relationship were all unaffected by HF. Combined AP and [Ca2+]i recordings demonstrated that the slower [Ca2+]i transient decay in HF SAN cells may result in increased INCX during the diastolic depolarization, but that this effect is likely counteracted by the HF-induced increase in intracellular Na+. β-adrenergic and muscarinic stimulation were not changed in HF SAN cells, except that late diastolic [Ca2+]i rise, a prominent feature of the Ca2+ clock, is lower during β-adrenergic stimulation. Conclusions: HF SAN cells have a slower [Ca2+]i transient decay with limited effects on pacemaker activity. Reduced late diastolic [Ca2+]i rise during β-adrenergic stimulation may contribute to an impaired increase in intrinsic frequency in HF SAN cells.